Effect of herbal cream containing Fumaria officinalis and silymarin for treatment of eczema: A randomized double-blind controlled clinical trial - Fariba Iraji; Behzad Sharif Makhmalzadeh; Mahya Abedini; Ali Aghaei; Amir Siahpoush (Mashhad University of Medical Sciences, 2022)
Objective: Atopic dermatitis (AD) is a common skin disorder with symptoms including severe pruritus and eczematous lesions. AD affects between 5 and 20% of people in their life. Silymarin (SM) is a polyphenolic flavonoid from Silybum marianum L.  and has several therapeutic characteristics including antiallergic, anticancer, and anti-inflammatory properties. Fumaria officinalis is a small plant that has a high antioxidant power and modulating effects on the immune system. Therefore, the current study intended to examine the influence of these two herbs extract on severity and symptoms of AD in patients.Materials and Methods: 40 patients with mild to moderate eczema randomly received mometasone 0.1% or the herbal cream. Treatment course was 2 weeks and patients were examined before and after 2 weeks of treatment using the SCORAD system.Results: The reduction of SCORAD score was significant in both groups (p=0.04 in the herbal group and p=0.03 in the mometasone group) but no significant difference was observed between the groups. Mean SCORAD score was 27.66±5.9 before therapy and 4.77±1.6 after therapy in the mometasone group and mean SCORAD score was 26.05±7.1 before therapy and 6.944±2.6 after therapy in the herbal group.Conclusion: The current study indicated the impact of these two herbs extract on severity and symptoms of AD in patients; these plants may be a new treatment in reducing eczema symptoms and its problems.